A study evaluating the awareness among general population towards common medical emergencies - Naqash, Mohd Mubarik; Salati, Sajad Ahmad; Bhat, Arif Nabi; Akram, Waseem; Gulzar, Ishfaq (International Journal of Research in Medical Sciences, 2017)
Background: Basic life support has been found to be lifesaving in common medical emergencies. The level of awareness about emergency care in general population and the approach of the common people with regards to common medical emergencies is an important determinant of positive outcome. Methods: This study was conducted in 445 participants randomly selected from visitors of our outpatient department, to study the awareness in general public about the medical emergencies and basic life support skills. Results: This study was conducted in 445 participants randomly selected from visitors of our outpatient department, to study the awareness in general public about the medical emergencies and basic life support skills. Conclusions: Awareness about common medical emergencies is low in general public and there is a need to devise strategies to improve this awareness.